2012
DOI: 10.1127/0935-1221/2011/0024-2126
|View full text |Cite
|
Sign up to set email alerts
|

Crystal defects in dense hydrous magnesium silicate phase A deformed at high pressure: characterization by transmission electron microscopy

Abstract: To cite this version:Alexandre Mussi, Patrick Cordier, Daniel J. Frost. Crystal defects in dense hydrous magnesium silicate phase A deformed at high pressure: characterization by transmission electron microscopy. European AbstractDense hydrous magnesium silicate (DHMS) Phase A has been deformed at 11 GPa, 700 and 400°C in the multianvil apparatus. Transmission electron microscopy (TEM) characterizations using the weak-beam dark-field (WBDF) 2 dislocations is observed in the basal plane. Furthermore, prismatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The occurrence of dislocations with Burgers vectors larger than 10Å raises the question of their stability. Frank (1951) dislocations with very large Burgers vectors (12.4Å) (Mussi et al, 2012). In garnets, Voegelé et al (1998) 16.3Å).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of dislocations with Burgers vectors larger than 10Å raises the question of their stability. Frank (1951) dislocations with very large Burgers vectors (12.4Å) (Mussi et al, 2012). In garnets, Voegelé et al (1998) 16.3Å).…”
Section: Discussionmentioning
confidence: 99%
“…This phase which deforms easily by basal glide and kinking, could have played a role in initiating subduction. Recently, we have performed, by transmission electron microscopy (TEM), a first study on the plastic deformation mechanisms of phase A at 11 GPa, 700 and 400 °C (Mussi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Poli and Schmidt, 1997). The sample investigated here was synthesised and deformed in the multianvil apparatus at the Bayerisches Geoinstitut, Bayreuth, Germany (Mussi et al , 2012). Phase A was synthesised from high purity oxides at 11 GPa (nominal pressure) and 900°C.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…The recovered samples were further deformed at 11 GPa and 700°C (run H3008). The first characterisations of crystal defects in phase A, performed by Mussi et al (2012) has shown that phase A was very sensitive to electron beam damage and TEM characterisation could only be performed under conditions adjusted to slow down beam damage, in particular using a liquid nitrogen cooling TEM holder. The structure of phase A is hexagonal, space group P 6 3 , with a = 7.8603 Å and c = 9.5730 Å (Horiuchi et al , 1979).…”
Section: Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation